0707 Effects of obstructive sleep apnea on Anti-SARS-COV-2 igg levels in older adults vaccinated against covid-19. (25th May 2022) - Pires, Gabriel; Andersen, Monica; Rosa, Daniela; Tufik, Sergio; Tufik, Sergio
Abstract: Introduction: Sleep disorders and sleep deprivation induces decreased antibody response following vaccination for different viral diseases (including H1N1, influenza and hepatitis A). The same has been speculated for COVID-19. This study aimed to assess whether obstructive sleep apnea (OSA) reduces antibody levels after COVID-19 vaccination among older adults. Methods: This was a convenience-sample study composed of older adults (≥60 years old). Those who underwent polysomnography at the Sleep Institute (São Paulo, Brazil) and received complete COVID-19 vaccination schedule were considered eligible. Individuals with previous diagnosis of COVID-19, less than 15 days between vaccination and IgG testing, or CPAP use in the last 3 months were excluded. Anti-SARS-CoV-2 IgG levels were measured using a chemiluminescence assay. The participants were distributed in the following groups, according to their apnea-hypopnea index (AHI): no/mild OSA (AHI<15), moderate OSA (AHI≥15 and <30) and severe OSA (AHI≥30). The effects of OSA on IgG levels (ANOVA), the correlation between IgG levels and AHI (Spearman's correlation test) and the association between serostatus (positive vs. negative) and OSA severity levels (X2 test) were analysed. Results were considered as statistically significant when p<0.05. Results: The sample included 122 older adults (median age 72.0 - IQR: 5.7), of whom 35 (28.6%) had AHI no/mild OSA; 31 (25.4%) had moderate OSA, and 56 (45.9%) had severe OSA. Oxford/AstraZeneca was the most referred vaccine (n=111, 91.0%), followed by CoronaVac (n=9, 9.0%). Seropositive status (IgG count ≥50.0 AU/mL) was observed in 90.2% of the participants and the median IgG levels in the complete sample was 273.0 AU/ML (IQR: 744.0). No/mild, moderate and severe OSA groups presented IgG levels of 482.0 (IQR: 677.0), 285 (IQR: 884.0) and 181.0 (IQR: 598.0), respectively, with no statistical difference them (p=0.606). There was no statistically significant correlation between AHI index and IgG levels (Spearman's rho=-0.169, p=0.063) and no significant association between serostatus and OSA severity groups (X2=0.912; p=0.634). Conclusion: Anti-SARS-CoV-2 IgG levels after vaccination are not significantly affected by OSA among older adults. Thus, despite being at higher risk for severe cases, OSA does not decrease the antibody response following vaccination against COVID-19. Support (If Any): AFIP, CNPq, CAPES